Pathogenicity and immunogenicity local isolat infectious laryngo tracheitis virus - Risa Indriani; Helmy Hamid; R.M Abdul Adjid; Muharam Saepulloh (Jurnal Ilmu Ternak dan Veteriner, 2004)
Infectious laryngotracheitis (ILT) is an acute and contagious respiratory diseases of chicken. The virus is Gallid herpes and belong to family herpesviridae. Two local strains of ILT virus those were BGR-6 and BKS-3 were isolated and their pathogenicity and immunogenicity were further observed after five time pareses on coris allantoic of specific pathogenic free embryonated eggs. The pathogenicity of both isolates to be possible for use as seed vaccine were detected based on pathogenicity indices and antibody response. Experimental specific pathogenic free chicken in isolator cages were infected by the isolates using103EID50. ILT virus per dose. Clinical syndromes, pathological anatomic lesions, and immunological response were observed in the infected chickens and another group at uninfected chickens as a control. Results showed that either BGR-6 or BKS-3 caused clinical signs with ITPI scores of 0,05 and 0,03 respectively and there were no mortality of infected chickens. The top antibody responces of BGR-6 and BKS-3 were observed at OD 0.90 and 0.44 respectively. It can be concluded that BGR-6 and BBS-3 had low ITPI scores, but BGR-6 gave higher antibody response and can be used as a candidate for seed vaccine.   Key words: Infectious laryngotracheitis, ILT, BGR-6, BKS-3, pathogenicity, immunogenicity